2021
DOI: 10.3390/antibiotics10121456
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mycobacterial F-ATP Synthase C-Terminal α Subunit Interaction Motif on Rotary Subunit γ

Abstract: Mycobacteria regulate their energy (ATP) levels to sustain their survival even in stringent living conditions. Recent studies have shown that mycobacteria not only slow down their respiratory rate but also block ATP hydrolysis of the F-ATP synthase (α3:β3:γ:δ:ε:a:b:b’:c9) to maintain ATP homeostasis in situations not amenable for growth. The mycobacteria-specific α C-terminus (α533-545) has unraveled to be the major regulative of latent ATP hydrolysis. Its deletion stimulates ATPase activity while reducing ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The ζ subunit of α-proteobacteria inhibits hydrolysis by binding to the interface of the αβ DP pair in a manner similar to IF 1 61 – 63 . Mycobacteria have a specific insertion sequence at the C-terminal of the α subunit called the α-extension loop 64 , 65 . Recent cryo-EM analysis showed that the α-extension loop binds to a specific loop on the γ subunit, which is considered to block rotation in a counterclockwise direction 26 , 66 .…”
Section: Discussionmentioning
confidence: 99%
“…The ζ subunit of α-proteobacteria inhibits hydrolysis by binding to the interface of the αβ DP pair in a manner similar to IF 1 61 – 63 . Mycobacteria have a specific insertion sequence at the C-terminal of the α subunit called the α-extension loop 64 , 65 . Recent cryo-EM analysis showed that the α-extension loop binds to a specific loop on the γ subunit, which is considered to block rotation in a counterclockwise direction 26 , 66 .…”
Section: Discussionmentioning
confidence: 99%
“…( 6) Another inhibitory protein named AtpΘ has been recently found in photosynthetic cyanobacteria; however, it is only a partial F O inhibitor of the cyanobacterial ATP synthase [18,19]. (7) A different inhibitory mechanism of latent ATP hydrolysis has also been described in mycobacteria, in which an extra C-terminus of the α subunit of about 3.5 kDa interacts with subunit γ [20,21] and leads to a novel anti-tuberculosis compound [22,23]. In summary, nature evolutively designed several F 1 F O -ATPase inhibitory proteins or domains to complement the insufficient kinetic and partial inhibitory MgADP regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Reconstitution of MsF-ATP synthase was carried out as described previously. 38 ATP Synthesis Assay. ATP synthesis was performed as described previously.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…ATP synthesis was performed as described previously. 38 Fluorescence Quenching Assay. A Varian Cary Eclipse spectrofluorometer was used, and all experiments were carried out at 20 °C.…”
Section: ■ Conclusionmentioning
confidence: 99%